Spatial Mapping of Myeloid Cells and Macrophages by Multiplexed Tissue Staining - Saylor, Joshua; Ma, Zhaoxuan; Goodridge, Helen S.; Huang, Fangjin; Cress, Anne E.; Pandol, Stephen J.; Shiao, Stephen L.; Vidal, Adriana C.; Wu, Lily; Nickols, Nicholas G.; Gertych, Arkadiusz; Knudsen, Beatrice S. (Frontiers in Immunology, 2018)
An array of phenotypically diverse myeloid cells and macrophages (MC&M) resides in the tumor microenvironment, requiring multiplexed detection systems for visualization. Here we report an automated, multiplexed staining approach, named PLEXODY, that consists of five MC&M-related fluorescently-tagged antibodies (anti - CD68, - CD163, - CD206, - CD11b, and - CD11c), and three chromogenic antibodies, reactive with high- and low-molecular weight cytokeratins and CD3, highlighting tumor regions, benign glands and T cells. The staining prototype and image analysis methods which include a pixel/area-based quantification were developed using tissues from inflamed colon and tonsil and revealed a unique tissue-specific composition of 14 MC&M-associated pixel classes. As a proof-of-principle, PLEXODY was applied to three cases of pancreatic, prostate and renal cancers. Across digital images from these cancer types we observed 10 MC&M-associated pixel classes at frequencies greater than 3%. Cases revealed higher frequencies of single positive compared to multi-color pixels and a high abundance of CD68+/CD163+ and CD68+/CD163+/CD206+ pixels. Significantly more CD68+ and CD163+ versus CD11b+ and CD11c+ pixels were in direct contact with tumor cells and T cells. While the greatest percentage (~ 70%) of CD68+ and CD163+ pixels was 0 – 20 microns away from tumor and T cell borders, CD11b+ and CD11c+ pixels were detected up to 240 microns away from tumor/ T cell masks. Together, these data demonstrate significant differences in densities and spatial organization of MC&M-associated pixel classes, but surprising similarities between the three cancer types.